Terms of engagement: The collaborative representation of Alutiiq identity - Crowell, Aron (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2004)
AbstractThe book and exhibition Looking Both Ways: Heritage and Identity of the Alutiiq People present both Alutiiq and anthropological perspectives on a complex Alaska Native ethnicity. This community-based project, produced by the Smithsonian Institution and Alutiiq Museum in Kodiak, is considered within several frames: cultural identity and revitalization in the Alutiiq region, the new paradigm of collaborative anthropology, and contrasting essentialist and constructivist models of cultural change. An Alutiiq “cultural logic” of connection to ancestors, kin, place and a provident natural environment is proposed as the basis for continuity of identity through two centuries of cultural transformation. Collaborative engagement in Indigenous heritage projects is discussed as a complex but indispensable commitment for contemporary anthropology.